Lipid bioproduction through optimization of thermal diluted acid pretreatment on native grass using Yarrowia lipolytica. (1st February 2023) - Satya Sagar, Polinati; Kommoji, Satish; Jayaraj, Iyyappan; Balakrishnan, Deepanraj; Shaik, Feroz; Vucha, Mahendra; Gnanasekaran, Lalitha
Graphical abstract: Highlights: Optimization of thermal diluted sulfuric acid pretreatment on native grass was performed. The maximum total reducing sugar was obtained at 163.8 °C, 1.57 % (v/v) of sulfuric acid concentration for 21 min. Pretreatment was performed without enzymatic hydrolysis. About 11.64 ± 0.84 g/L of lipid was produced in a 5 L fermentor. Abstract: In the present study, thermal-dilute sulfuric acid pretreatment was performed on native grass ( Cyperus distans ) biomass for achieving optimized simple sugar recovery. Lipid bioproduction was performed using Yarrowia lipolytica from pretreated native grass biomass. Optimization of thermal diluted acid pretreatment on native grass biomass was investigated using one factor at a time (OFAT) method and response surface methodology. The maximum total reducing sugar (34.26 ± 1.55 g/L) in native grass hydrolysate was obtained at 163.8 °C, 1.57 % (v/v) of sulfuric acid concentration for 21 min. Minimization of formed inhibitors was performed using detoxification. About 11.64 ± 0.84 g/L of lipid was produced with 65.52 % (w/w) of lipid content after 96 h from detoxified native grass hydrolysate using Y. lipolytica in a 5 L fermentor. Result revealed that optimization of thermal diluted acid pretreatment on native grass biomass is an efficient method for lipid production using Y. lipolytica .